Description of palatal rugae size and direction in children with gender difference - Nur, Muhammad Arfianto; Djustiana, Nina; Malinda, Yuti (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: Indonesia has a high number of children victims of disaster in the last five years, but the children do not have identity cards, causing difficulties in the identification process. Palatal rugae are considered unique in individuals, and their morphology remains stable throughout life. Data of palatal rugae pattern in children aimed to facilitate the process of identification of the childs gender. The purpose of this research was to discover the description of palatal rugae in children which can be used as a reference of gender identification in children. Method: A descriptive research design was performed with purposive sampling method.Â Samples were taken from 119 maxilla images consisted of 69 images of girls maxilla and 50 images of boys maxilla. The study was performed by taking individual maxilla images with intraoral mirror and observing towards the direction of the palatal rugae according to the Carrea classification, and the size of palatal rugae according the Lysell classification. Results: The type IV direction and secondary size of palatal rugae were found to be dominant on both sides of maxilla in boys and girls. Conclusion: Palatal rugae in boys and girls were having the same direction which was the type IV, and the size of secondary rugae was found to be dominant on both sides of the palate. Palatal rugae also proofed to be able to become the complementary method for determining unidentified gender in children.